A new perspective on trait differences between native and invasive exotic plants. Issue 2 (1st February 2014) - Leffler, A. Joshua; James, Jeremy J.; Monaco, Thomas A.; Sheley, Roger L.
Abstract : Functional differences between native and exotic species potentially constitute one factor responsible for plant invasion. Differences in trait values between native and exotic invasive species, however, should not be considered fixed and may depend on the context of the comparison. Furthermore, the magnitude of difference between native and exotic species necessary to trigger invasion is unknown. We propose a criterion that differences in trait values between a native and exotic invasive species must be greater than differences between co‐occurring natives for this difference to be ecologically meaningful and a contributing factor to plant invasion. We used a meta‐analysis to quantify the difference between native and exotic invasive species for various traits examined in previous studies and compared this value to differences among native species reported in the same studies. The effect size between native and exotic invasive species was similar to the effect size between co‐occurring natives except for studies conducted in the field; in most instances, our criterion was not met although overall differences between native and exotic invasive species were slightly larger than differences between natives. Consequently, trait differences may be important in certain contexts, but other mechanisms of invasion are likely more important in most cases. We suggest that using trait values as predictors of invasion will be challenging.